The lion, the witch, and the wardrobe book 2 - Lewis, C. S.; Baynes, Pauline (HarperTrophy London, 2009)
Four English schoolchildren find their way through the back of a wardrobe into the magic land of Narnia and assist Aslan, the golden lion, to triumph over the White Witch, who has cursed the land with eternal winter